2009
DOI: 10.1021/np900572g
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents of the Stem Bark of Mitrephora glabra

Abstract: Bioactivity-guided fractionation of the stem bark of Mitrephora glabra yielded nine compounds, comprising three ent-kaurenoids (1-3), five polyacetylenic acids/esters (4-8), and one aporphine alkaloid, liriodenine (9). The structures of the six new compounds (1-3, 5, 7, and 8) were determined by spectroscopic data interpretation. All compounds were evaluated for their inhibitory activities against a panel of cancer cell lines and a battery of microorganisms.Over the last two decades, plants of the Annonaceae h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9]. Polyynes were regarded to be responsible for many bioactivities of Oplopanax horridus, which has long history of medicinal use and as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%
“…To date, pharmacological investigations have revealed that polyynes from natural sources show antibacterial, anti-fungal, antiinflammatory, nerotoxic and anticancer activities [6][7][8][9]. Polyynes were regarded to be responsible for many bioactivities of Oplopanax horridus, which has long history of medicinal use and as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed by, the HMBC correlations from H-11 ( H 5.00, dd, J = 3.7, 3.1 Hz) to C-8 ( C 45.9, C), C-10 ( C 38.1, C), and C-13 ( C 38.8, CH), as shown in Figure 1. The α-orientation of the carboxylic acid group at C-4 was inferred from the 13 C NMR chemical shift of the methyl group at C-4 by comparing those of related entkaurane diterpenoids, in which the methyl group with β-orientation resulted in resonance of approximately δ C 29, as opposed to resonance of approximately δ C 16 when the methyl group was in the α-orientation. 7,13,14 Accordingly, the structure of compound 2 was elucidated as ent-17-hydroxykaura-9 (11) , resembled those of (3R,4R,6S)-3,6-dihydroxymenth-1-ene.…”
Section: Resultsmentioning
confidence: 99%
“…octadeca-9,11,13-triynoic acid [10] (2), (13E)-octadec-13-en-9,11-diynoic acid [11] (3), (13E)-octadec-13-en-11-ynoic acid [9] (4), lupenone [12] (5), β-amyrone [13] (6), and (S)-sambunigrin [14] (7) was elucidated through comparison with literature data. The acetylenic products are usually unstable, undergoing photolytic or pH-dependent oxidation leading to their decomposition [15].…”
Section: Resultsmentioning
confidence: 99%